The Effect of Nitrogen Stress And Photoperiode on Growth and Fatty Acid Content of Nannochloropsis sp. - Dini Ermavitalini; Sumarni Dwirejeki; Sri Nurhatika; Triono Bagus Saputro (Akta Kimia Indonesia, 2019)
Energy consumption increases from year to year and 95% is fulfilled by fossil materials which are limited, so that a replacement energy source is needed. Biodiesel is a fuel from renewable sources such as plants or animals. Biodiesel from Jatropha curcas and palm oil has been produced but oxidation is low in cold temperatures and long time to production. On the other hand, Nannochloropsis sp., as marine microalgae can produce lipids as biodiesel material reaches 90% of the biomass dry weight in stress condition, It’s higher than lipid that produced by Jatropha curcas (35% DW) and palm (75,6% DW). Nannochloropsis sp. also short growth, easily propagated. Production of lipids and TAGs of  Nannochloropsis sp. can be engineered based on nutrient, temperature, aeration, salinity, photoperiod. This study aims to examine the effect of nitrogen stress and photoperiode on biomass, chlorophyll content, fatty acid profile, content of TAG. Nannochloropsis sp. cultured from the starter then cultured in variation of nitrogen stress and phoroperiode.  In the last exponential, culture analized in quantitative to get the biomass and chlorophyll content. Fatty acid and TAG analized by qualitative. The interaction between nitrogen and photoperiode did not affect the biomass of  Nannochloropsis sp. but it affects the chlorophyll content where the chlorophyll content of P14 (N100, 16: 8) is 7.367 mg/L. It is not significantly different from the treatment P6 (N25, 24: 0) of 3.339 mg/L and treatment P15 (N100, 24: 0) 5.665 mg/L. All cultures with a treatment combination showed triacylglycerol content. The results of the treatment of fatty acid profiles P14 (N100, 16: 8) contain more varied fatty acids compared to P1 (N0, 12:12), P2 (N0, 16: 8), P8 (N50, 62: 8), P10 (N75 , 12:12) which consists of lauric acid, hexagonal acidrionate, palmitic acid, linoleic acid, oleic acid, stearate acid, eicosanoic acid.The result showed that the treatment of nitrogen stress and photoperiode affecting the growth and fatty acid content of Nannochloropsis sp.